Balance de los procesos de descentralización y participación social en salud en Colombia en la década de los 90 (2000)
ABSTRACT: This essay analyses different paper wrote in the country about decentralization and participation and complements them with interviews to experts. It shows that the process of decentralization and participation began very late in our country, that he towns have emphasized the development of physical structures, that health plans are not thought according to those of development, and social security and focalization replace territorial perspective of public health management, taking the place of public health actions and programs. As for participation, multiplicity and superimposition of organizational forms and mechanisms and the limited decisive capability formulates in laws along with low democratic sector tradition have all fragmented the already precarious social and citizen health initiatives.